Catalyzing the use of climate information in agriculture decision making through datahubs - Dhulipala, Ram; Joseph, Jacob Emanuel; Konte, Oumar; Faye, Aliou; Worou, Nadine; Whitbread, Anthony M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This infonote describes the importance of digital data ifrastructure like data hubs in enhacing the use of climate and weather data in agriculture policy making, extension as well as farm level decision making. Taking Senegal as a case study, the infonote use a value chain framing to map out the key actors in the Climate Information Services (CIS) data value chain and the importance of the proposed AgDataHub